Comparison of sampling and spectrophotometric determination of ammonia using nesslerization with standard ion chromatography in air monitoring of workplaces. Issue 8 (21st June 2023) - Mirzaei, Ahmad; Neghab, Masoud; Yousefinejad, Saeed
ABSTRACT: In this study, for the first time a comparison was done between sampling method of ammonia using NIOSH 6016 followed by spectrophotometry based on Nessler reagent (EPA method 350.2) to show the potential of spectrophotometry for determination of airborne concentrations of ammonia in occupational media. The study was performed in two phases. The first phase involved static preparation of different concentrations of ammonia, ranging from 0.02 to 0.4 mg in 5 L of air followed by sampling from these concentrations and extraction/analysis based on NIOSH 6016 spectrophotometric method. The average recovery of analysis in step 1 was 94.90%. In the second phase, 33 air samples, collected from a petrochemical company, were analysed by both spectrophotometry and ion chromatography approaches. A very good correlation (R 2 = 0.9974) was found between the two methods. The results showed that combination of sampling and extraction noted in NIOSH 6016 with the analysis approach based on Nessler reagents can be assumed as a précised, reliable, easy and applied method for the evaluation of short/long-time personal exposures and also environmental concentrations in occupational places.